Auroral pulsations and accompanying VLF emissions - Tagirov, V. R.; Ismagilov, V. S.; Titova, E. E.; Arinin, V. A.; Perlikov, A. M.; Manninen, J.; Turunen, T.; Kaila, K. (CCSD, 1999)
International audience Results of simultaneous TV observations of pulsating auroral patches and ELF-VLF-emissions in the morning sector carried out in Sodankylä (Finland) on February 15, 1991 are presented. Auroral pulsating activity was typical having pulsating patches with characteristic periods of about 7 s. Narrow-band hiss emissions and chorus elements at intervals of 0.3?0.4 s formed the main ELF-VLF activity in the frequency range 1.0?2.5 kHz at the same time. The analysis of auroral images with time resolution of 0.04 s allowed perfectly separate analysis of spatial and temporal variations in the auroral luminosity. Mutual correspondence between the behaviour of the luminous auroral patches and the appearance of ELF noise type hiss emissions and VLF chorus trains was found in two intervals chosen for analysis. While the hiss emissions were associated with the appearance of luminosity inside a limited area close to the zenith, the structured VLF emissions were accompanied by rapid motion of luminosity inside the area. The spatial dimension of the pulsating area was about 45?50 km and luminosity propagated inside it with velocity of about 10?12 kms. We discuss a new approach to explain the 5?15 s auroral pulsation based on the theory of flowing cyclotron maser and relaxation characteristics of ionosphere.